Induksi Kalus Jeruk Kasturi (Citrus microcarpa) Menggunakan Hormon 2,4-D dan BAP dengan Metode in vitro - Imam Mahadi; Wan Syafi’i; Yeni Sari (Jurnal Ilmu Pertanian Indonesia, 2016)
Calamansi fruits (Citrus microcarpa) or musk lime is one horticulture crops has been known as beverage and food flavorings. This research aimed to determine the effect of 2,4-D and BAP on callus induction of explants calamansi fruits (Citrus microcarpa). Parameters observed is percentage of explants, time appeared callus, callus width, and texture of the callus. Research results and a growing percentage of the width callus explants were analyzed by ANOVA and a further test DMRT at 5% level. The next to appear callus timing parameters and texture of callus analyzed in description. The result shows that a combination of hormones D4B1 and D4B2 produces a callus emerged fastest of 3.3 days after culture. The highest percentage of callus formation that is 100% contained in the treatment of D2B0, D2B0.5-D4B0. The mean width of callus was highest in treatment D4B2with a width of 0.97 cm. Embryogenic callus resulting by treatment of D2B1, D2B2, and D3B0. However, the best a combination of hormones is treatment D2B2 (2 mg/l, 2,4-D, dan 2 mg/l BAP) producing embryogenic callus edvanced to suspension cultures.